(untitled) (SADGAMAYA, 2026)
The purpose of this research is to examine the impact of HR interventions, specifically training, recruitment policies, and support from supervisors, on employee absence using biometric attendance. Quantitative approach using self-administered questionnaire was used to collect the data. The study focused on a population of 2,422 individuals, from which a sample of about 250 participants was chosen. This sample size was selected to accurately reflect the broader population, allowing for meaningful insights while keeping the data collection process practical and manageable. By choosing this sample, the study aims to ensure the results are both reliable and applicable to the larger group. The results show that HR interventions have a significant impact on reducing employee absence, with the strongest effect seen in the use of biometric attendance. The findings provide valuable information for companies to better understand the importance of HR interventions and the role of biometric attendance in reducing employee absence as well as contributes to provide valuable insights for organizations seeking to enhance workforce attendance and overall productivity.